ANALISIS KARAKTER SISWA KELAS II SD NEGERI 04 PAYARAMAN PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Agung Rizky Wirayuda; Allen Marga Retta; Puji Ayurachmawati (STKIP Subang, 2024)
The problem of this research is that character education is a lesson that must be implemented in every school in order to prevent incidents that have a bad impact. This research aims to find out whether there are forms of character education in classroom learning activities and to find out how to cultivate character for class II students at SD Negeri 04 Payaraman. Formulation of the problem: how to embed character education in class II learning activities at SD Negeri 04 Payaraman? The research uses qualitative with descriptive methods. Data collection techniques through observation, documentation and interviews. Data analysis techniques using. Researchers used the Miles and Huberman model of data analysis which includes three stages, namely data reduction, data display, and drawing conclusions. The results of the research show that students at SD Negeri 04 Payaraman have high character attitudes. This is known from the results of research conducted on students using questionnaires and supported by interviews which include three indicators of character implementation including, disciplinary attitude: students are able to apply 3 indicators of discipline, caring attitude: students are able to apply 3 indicators of caring and cooperative attitude: students are able apply 3 indicators of cooperation. This shows that class II students at SD Negeri 04 Payaraman have a very high category of character attitudes. Thus, it can be concluded that students at SD Negeri 04 Payaraman school on average have high character attitudes.